SURVEI KEPADATAN ARUS LALU LINTAS DI PERSIMPANGAN PENCENG JALAN RA. RUKMINI, KECAPI KEBUPATEN JEPARA - Heni Yustianah; Istianah Istianah (Universitas Tidar, 2017)
Traffic density is the size or volume of vehicles passing through the road in a particular area with varying vehicle currents at certain hours of time stated in hourly per kilometer. This research was conducted at the intersection of RA roadblocks. Rukmini Kecapi Jepara District to know the density of traffic flow in the area. From the results of the study showed that the presence of traffic density in the morning and afternoon in due to the activity of the students, students, employees and public vehicles simultaneously. Keywords: Density, Traffic, bawu penceng.